Bioventilação em um solo argiloso contaminado com mistura de diesel e biodiesel - Reginatto, Cleomar (2012)
The intense and growing consumption of fossil fuels generates the need to seek more environmentally suitable alternative. So to meet this need, enters in the market the biofuels as is the case of biodiesel, which is now being mixed in a ratio of 5% commercial diesel and will come in 20% (B20) in the near future.Thus this mixture turns out to be a likely contaminant of soil and water resources, as well as diesel. Several processes are used for remediation and restoration of contaminated soils. Some of these processes involve the use of microorganisms to degrade and decontaminate the soil. The microorganisms are considered biodegraders efficient due to its abundance, species diversity, catabolic and anabolic versatility and its ability to adapt to adverse environmental conditions. Among the biological techniques, the bioventilação can be used mainly due to the low cost of implementation and low degree of intervention in the contaminated area, since it involves only the insertion of air in the middle, to stimulate the activity of aerobic microorganisms natives. Thus, the aim of this work was to evaluate the bioremediation of a clay soil contaminated with a mixture B20 using the technique of Bioventing. The experiments (bioreactors) were performed at the Laboratory of Geotechnics Environmental at the University of Passo Fundo. In tests of bioventilação were tested three different airflow rates (2.4 and 6 L / min), and a control without application of the technique in three time intervals (1 hour for each 24 hours, 1 hour for each 36 hours and 1 hour for each 48 hours ) during 6 days a week. The experiments were analyzed in four times of degradation (15,30,60 and 120 days). The degradation of the contaminants was analyzed quantitatively by extraction by ultrasound, qualitatively through the degradation of the carbon chains by gas chromatography, and enzyme activity (FDA) and plate count. The results showed the greatest degradation at the end of 120 days for sample V2-1/48 with 87.72%, and lowest degradation for the natural attenuation, with 71, 54%, with statistical differences only for the natural attenuation in relation to all other samples. The enzymatic activity and microbial growth indicated an intense process of adaptation to the contaminant and not yet stabilized its activity. The qualitative results showed greater degradation of the fraction of light hydrocarbons, mainly of the carbon C15 to C18. Thus among the different combinations of flow and application time the best value was 4L/min flow and the best time interval of 1 hour applied each 48 hours. The bioventilação technique is efficient for the contaminant degradation compared with the natural attenuation.